The Effectiveness of Moringa Oliefera Pudding to Change Nutritional Status in Stunted Toddlers - Virgia, Vera; Herlina, Herlina (Jurnal MIDPRO, 2024)
The high prevalence of stunting is a priority that must be resolved with abundant local food sources and high nutritional content, one of which is Moringa leaves (Moringa oleifera). Moringa leaves are one of the interventions that can be used to prevent stunting. Moringa oleifera (moringa plant) is a widespread and easy cultivated plant in Indonesia with the potential for ergonomic, cheap and nutritious food additives. Many communities have widely used moringa plants. Stunting is a global health problem that affects 165 million children around the world. The global prevalence rate of toddlers/children with stunting incidence in 2020 is 22% or around 149.2 million children who are stunted. This study aims to determine the efficacy of Moringa Oliefera pudding in preventing child stunting. This study used a quasi-experimental approach, where one group of pre-test and post-test was used as a research design. A total of 33 children were selected as survey respondents. The results showed that Moringa Oliefera pudding consumption was effective in significantly increasing children's height and weight, with a p-value of 0.000 (< 0.05).